2001
DOI: 10.1093/carcin/22.3.489
|View full text |Cite
|
Sign up to set email alerts
|

Catechol estrogen conjugates and DNA adducts in the kidney of male Syrian golden hamsters treated with 4-hydroxyestradiol: potential biomarkers for estrogen-initiated cancer

Abstract: Formation of depurinating adducts by reaction of catechol estrogen-3,4-quinones with DNA was proposed to be a tumor initiating event by estrogens [E.L. Cavalieri et al. (1997) Proc. Natl Acad. Sci. USA, 94, 10937-10942]. Under estrogenic imbalance, oxidation of catechol estrogens to quinones may compete with their detoxification by protective enzymes. The quinones formed can be detoxified by reaction with glutathione (GSH) or can covalently bind to DNA. To provide more support for this hypothesis, we developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…Figure 3 is an overlay of a single EC detector channel (240 mV) for eight samples representing 20-fold lower metabolite levels. These signals are due to pg quantities of analyte on column and are consistent with reported 10 to 1000-fold lower limits of detection obtained with EC-Array when compared to photodiode array detection [19,40].…”
Section: Xenobiotic Toxicity Studiessupporting
confidence: 89%
See 1 more Smart Citation
“…Figure 3 is an overlay of a single EC detector channel (240 mV) for eight samples representing 20-fold lower metabolite levels. These signals are due to pg quantities of analyte on column and are consistent with reported 10 to 1000-fold lower limits of detection obtained with EC-Array when compared to photodiode array detection [19,40].…”
Section: Xenobiotic Toxicity Studiessupporting
confidence: 89%
“…Several analytical techniques are useful for metabolomics including gas chromatography with mass spectrometry (GC-MS) [15,16], liquid chromatography with coulometric array electrochemistry [17][18][19][20][21] (LC-ECArray), LC-MS [22][23][24], and nuclear magnetic resonance spectroscopy (NMR) [5,8,10,25]. The qualitative characteristics of techniques, such as MS and NMR, provide essential data for chromatographic peak identification and purity, structural elucidation, and for normalizing multivariate data.…”
mentioning
confidence: 99%
“…Cavalieri et al showed that 4-OHE 2 , when converted to its corresponding quinone and semiquinone metabolites, covalently binds purines in DNA, and this reaction results in the formation of abasic sites (91). Several studies have subsequently arisen that have shown that these abasic sites are present in vivo and contribute to carcinogenesis (94)(95)(96)(97)(98)(99). These studies have also shown that catechol estrogen quinones bind proteins within the cell, further contributing to carcinogenesis (94).…”
Section: Estrogen Metabolismmentioning
confidence: 99%
“…Although both LC-MS [15][16][17][18][19][20] and GC-MS [15,16,[21][22][23] have been used for the rapid and sensitive identification of estrogens and their metabolites, GC-MS usually requires derivatization which adds to the complexity of sample preparation, increases the time required per analysis, and might introduce artifacts. To eliminate the need for sample derivatization, we developed a method based on LC-MS-MS. From among the solution-phase ionization methods that have been reported for the mass spectrometric analysis of estrogens, such as fast atom bombardment (FAB) [24,25], atmospheric pressure chemical ionization (APCI) [15,19], and electrospray [15,16,20,25,26], we selected electro-spray ionization.…”
mentioning
confidence: 99%